Empagliflozin improves primary haemodynamic parameters and attenuates the development of atherosclerosis in high fat diet fed APOE knockout mice. (20th August 2019) - Dimitriadis, Georgios K.; Nasiri-Ansari, Narjes; Agrogiannis, Georgios; Kostakis, Ioannis D.; Randeva, Manpal S.; Nikiteas, Nikolaos; Patel, Vanlata H.; Kaltsas, Gregory; Papavassiliou, Athanasios G.; Randeva, Harpal S.; Kassi, Eva
Abstract: The effects of long-term treatment with empagliflozin on biochemical and immunohistochemical markers related to atherosclerosis and atherosclerosis development in the aorta of apolipoprotein E knockout [Apo-E (−/−) ] mice were evaluated in this study. Empagliflozin-treated mice had lower total cholesterol (P < 0.05), fasting glucose (P < 0.01), heart rate (P < 0.01) and diastolic blood pressure (DBP) (P < 0.05) compared to controls. Histomorphometry revealed reduced atherosclerotic lesion progress approaching statistical significance (P = 0.06) and approximately 50% wider lumen area for the Empagliflozin treated mice group. Although empagliflozin significantly reduced Vcam-1 and Mcp-1 ( P < 0.05, P < 0.01, respectively) and marginally induced Timp-1 and Timp- 2 mRNA expression (P < 0.08, P = 0.1 respectively), immunohistochemistry revealed a marginal reduction in VCAM-1 and MMP-9 (P = 0.1) without affecting the expression of TIMP-2 and MCP-1 in atherosclerotic lesions. Empagliflozin improves primary haemodynamic parameters and attenuates the progression of atherosclerosis by reducing hyperlipidemia and hyperglycemia, while direct actions in aorta vessel mediated via SGLT-1 are strongly hypothesized. Highlights: Empagliflozin reduces heart rate and diastolic blood pressure in APOE (−/−) mice. Empagliflozin reduces total cholesterol and increases HDL cholesterol. Empagliflozin reduces atherosclerotic lesion formation. Empagliflozin reduces VCAM-1 and MCP-1 inflammatory molecule expression.